STATE INFORMATION RESOURCES IN THE FIELD OF AIR TRANSPORT SYSTEM OF UKRAINE: TERMS AND DEFINITIONS - Юдін, О. К.; Іваннікова, В. Ю; Гирич, С. Ю. (Science-based technologies, 2016)
Modernization of air transport infrastructure in line with international requirements is an important part of the development strategy of our state at the world market. According to statements of the World Economic Forum; one of the bases for the state development at this market is usage of information technologies in key areas of its life activity; especially in aviation. So; today protection of state information resources (SIR) in the field of air transport system of Ukraine is one of the main priorities of our state in the area of ​​its national safety provision. However; conducted analysis of existing literature in the field of SIR of air transport system of Ukraine shows the absence of the given resources classification for air transport. In addition; a legal document about definition of air transport system SIR and its composite parts hasn’t been developed yet; as well as the place of the Ukrainian segment of the given electronic resources in the global space of objects identifiers hasn’t been determined. That’s why; on the basis of conducted researches the question of SIR definition in the field of air transport has been considered for the first time in the article. The actuality of further development of this question in Ukraine for its national safety is shown. The structure of the air transport system of Ukraine is presented. It was conducted the legal analysis; on the basis of which the definition of state information resources of air transport system of Ukraine has been formulated.